POLITICAL ISLAM AND THE ANTI-CAPITALISM NARRATIVE OF HIZBUT TAHRIR INDONESIA - Aswar, Hasbi; Faiz, Ihda Arifin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research will discuss the narrative of anti-capitalism from the perspective of the Islamic political movement by studying Hizbut Tahrir Indonesia's thoughts on the political-economic system in Indonesia. To date, capitalism has been a topic of global discussion, generating criticism due to various damages and social impacts in different countries. This study explores Hizbut Tahrir Indonesia's approach in responding to the influence of capitalism through the Islamic ideology they stand for. This research employs a qualitative approach by collecting data through documents and literature and analyzing it through a framing approach in social movement studies. The results showed that Hizbut Tahrir Indonesia views capitalism as a system that does not follow Islamic principles and produces injustice, inequality, and oppression against society. Hizbut Tahrir Indonesia presents an alternative Islamic-based political and economic system to solve the problems of capitalism in Indonesia and calls to implement sharia within the framework of an Islamic state or caliphate.